Investigation of velocities of saltating particles in a water stream - Tan, Chian Shieh. (2012)
This report carries out the investigation of velocities of round particles travelling in a water stream. Spherical beads are placed in a water stream in a regular rectangular channel with differing bed layers. A video system is used to study the saltation of the beads in an open channel flow. Image acquisition at an interval of up to 0.05 seconds is used to capture the saltating motion of the beads. From the images captured, the horizontal velocity of the beads is derived.